2023
DOI: 10.3389/fped.2023.1080194
|View full text |Cite
|
Sign up to set email alerts
|

Clinical thought-based software for diagnosing developmental dysplasia of the hip on pediatric pelvic radiographs

Abstract: BackgroundThe common methods of radiographic diagnosis of developmental dysplasia of the hip (DDH) include measuring hip parameters and quantifying the degree of hip dislocation. However, clinical thought-based analysis of hip parameters may be a more effective way to achieve expert-like diagnoses of DDH. This study aims to develop a diagnostic strategy-based software for pediatric DDH and validate its clinical feasibility.MethodsIn total, 543 anteroposterior pelvic radiographs were retrospectively collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Previous work has shown that, at 4.5 months of age, when the femoral head is predominantly cartilaginous, ultrasound is most effective [22]. In addition, conventional anteroposterior pelvic radiographs are more beneficial [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that, at 4.5 months of age, when the femoral head is predominantly cartilaginous, ultrasound is most effective [22]. In addition, conventional anteroposterior pelvic radiographs are more beneficial [23].…”
Section: Introductionmentioning
confidence: 99%